Development and Characterization of Butenafine Hydrochloride Solid Lipid Nanoparticles for Skin Targeting - Kazi, Anis.J.; Dharashive, Dr. Vishweshwar M.; Waghmare, Harsh. A.; Rudrurkar, Mukta.R. (Asian Journal of Pharmaceutical Research and Development, 2025)
Fungal infections are a common cause of skin diseases and their occurrence is increasing worldwide. Oral therapy for fungal infections can have toxic effects, require long treatment durations, and may not be well tolerated by patients. On the other hand, topical therapy for superficial fungal infections faces challenges such as poor solubility of drugs, skin irritation, and limited permeability through the skin. To address these challenges, solid lipid nanoparticles containing antifungal drugs, specifically Butenafine solid lipid nanoparticles (BUTE-SLN), were prepared for improved drug penetration, minimized side effects, and rapid relief from fungal infections. These nanoparticles were incorporated into a Carbapol gel base to enhance drug penetration through the skin and improve therapeutic activity. The BUTE-SLN was prepared using a modified solvent emulsification technique, and its formulations were evaluated for particle size, polydispersity index, zeta potential, entrapment efficiency, and drug loading. Furthermore, stability studies as per ICH guidelines confirmed the stability of the SLN dispersions. The BUTE-SLN were then incorporated into Carbapol gel in order to improve drug penetration and provide an additive effect in the treatment of fungal infections. The BUTE-SLN gel exhibited non-Newtonian pseudoplastic flow, excellent spreadability, ease of application, and adhesion. Furthermore, it was found to be occlusive, preventing transmembrane water loss, and showed greater skin hydrating potential than a marketed cream. In vitro drug release studies revealed a biphasic release pattern, with initial burst release followed by sustained release, indicating quick onset of action and prolonged antifungal effect. Skin retention studies demonstrated the maximum concentrations of drug in the stratum corneum. The BUTE-SLN gel exhibited enhanced antifungal activity and stability over the study period. The formulation of antifungal drugs into solid lipid nanoparticles for topical drug delivery proves to be a promising carrier for drug delivery, offering enhanced penetration and proven safety and compatibility